The Addition of Rosella Petal Filtrate (Hibiscus sabdariffa) in Egg Yolk Tris Diluent in Kaligesing Goat Frozen Semen - Fuadatin, Dwi Rosyidatu; Hariani, Dyah (LenteraBio : Berkala Ilmiah Biologi, 2024)
The genetic preservation of superior goat breeds can be done by storing spermatozoa at -196°C. The quality of goat spermatozoa can maintained by adding antioxidants in their diluting medium. The purpose was to determine the effect of rosella petal filtrate (FR) in egg yolk tris diluent (TKT) on the quality of Kaligesing goat spermatozoa. The type of experimental study using a complete randomized design (RAL) had 4 treatments (FR 0.0%, 1.5%, 3.0%, and 4.5%) with 5 repeats. The parameters observed include motility, viability, and integrity of spermatozoa cell membranes. The data was analyzed statistically using one-way ANOVA test continued with Duncan test. The ANOVA test showed a significant effect on the quality of Kaligesing goat spermatozoa (P<0.05) by administration of petal filtrate in the TKT diluent. The concentration of 3% FR filtrate was found to be the best concentration to maintain the quality of Kaligesing goat spermatozoa at storage temperature of -196℃, with sperm motility recorded at 40,10±4,93%, viability at 57,82±5,71%, and membrane integrity at 51,78±5,15% compared to other concentrations.